2021
DOI: 10.1029/2020gl090782
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Continuous Monitoring of Borehole Displacements Induced by Stimulated Hydrofracture Growth

Abstract: We provide direct observations of the three‐dimensional displacements of a fluid‐driven fracture during water injections in a borehole at ∼1.5 km depth in the crystalline rock at the Sanford Underground Research Facility (USA). Micro‐shearing of the borehole initiates on a foliation plane at 61% of the minimum principal stress σ3. As the fluid pressure increases further up to 112% of σ3, borehole axial and radial displacements increase with injection time highlighting the opening and sliding of a new hydrofrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Pressure slowly declined until 21:56:40 UTC (p = 23.5 MPa), when it slowly increased until the end of injection at 22:05:16 UTC (p = 26.3 MPa). The development of the hydraulic fracture during this test and several re-opening and propagation cycles is described in Guglielmi et al (2021).…”
Section: Overview Of Hydraulic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure slowly declined until 21:56:40 UTC (p = 23.5 MPa), when it slowly increased until the end of injection at 22:05:16 UTC (p = 26.3 MPa). The development of the hydraulic fracture during this test and several re-opening and propagation cycles is described in Guglielmi et al (2021).…”
Section: Overview Of Hydraulic Testingmentioning
confidence: 99%
“…Here we present direct observations in support of the pre-slip model from a series of meso-scale injection experiments performed at 1480 m depth. Using passive seismic monitoring and in-situ displacement sensors sensitive to µm-scale deformation and rotation we closely tracked the initiation of a hydraulic fracture, i.e., an opening mode fracture that propagates for pore fluid pressures greater than the least principal stress (Guglielmi et al, 2021). During the pressurization stage, and before the initiation of the hydraulic fracture, we observed the slippage caused by a single shear event including its pre-slip, co-seismic and afterslip phases.…”
Section: Introductionmentioning
confidence: 99%
“…With the large number of in-situ experiments currently being performed at various underground laboratories (e.g. Guglielmi et al 2020Guglielmi et al , 2021Ma et al 2020;Schoenball et al 2020), it is important to understand which processes may be relevant in the near field of a stimulated fault/fracture. The development of new high-frequency sensors will allow for more detailed measurements of dynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [11,12] showed that the anchor bolt not only provides supporting force on the roadway surface but essentially forms a load-bearing structure with certain strength through the coupling action of anchor bolt and surrounding rock. In literature [13][14][15], the stress evolution, displacement field, local deformation, overall distribution, and destroy characteristics of surrounding rock anchoring structures were studied with different bolt spacing through model tests. In literature [16,17], the influence of bolt preloading force and bolt spacing on the supporting strength of surrounding rock anchoring structure through numerical simulation software was analyzed, the supporting scheme of excavation roadway was designed, and the effectiveness of the supporting scheme by adopting the roadway displacement measurement scheme was verified.…”
Section: Introductionmentioning
confidence: 99%